Kontrol Kecepatan Berbasis PWM (Pulse Width Modulation) Untuk Mesin Pemarut Kelapa Bertenaga Surya - Fadhillah Hazrina; Riyani Prima Dewi; Betti Widianingsih; Laura Sari; Mifta Zulfahmi Muassar (Infotekmesin, 2025)
Solar energy is a new renewable energy (EBT) that can be used as an alternative energy source for electricity generation to replace fossil fuels or supplies from the National Electricity Company (PLN). One of its uses can be applied in everyday life in household appliances, namely, coconut grater machines. Coconut grater machines used in the market still use fossil fuels to crush coconut meat, so solar energy is implemented as an alternative energy to operate the coconut grater machine. The use of solar panels in this study is highly dependent on sunlight exposure. In addition, the tilt position of the solar panel can also determine the power generated by the solar panel. The tilt position of the solar panel can be manually adjusted according to the direction of sunlight at certain times. Around midday, sunlight can be captured optimally. At that time, the accumulator/battery will quickly charge, and the coconut grater machine can be used at low or high speeds. The purpose of this study is to implement a PWM (Pulse Width Modulation) system-based control as a motor speed regulator on a coconut grater machine. PWM technology is installed to obtain optimal rotation results and has the potential to save electrical energy. The research results showed that the installed solar panels could produce an average of 4.86 watts of electrical power at 8:00 a.m. WIB and a maximum of 5 watts of electrical power at 12:00 p.m. WIB. Under no-load operating conditions, the current was 0.38 A and the motor speed was 3,724 Rpm. When the engine was tested under load, the speed was 2,926 Rpm.